VIM thalamic stimulation for tremor in a patient with IgM paraproteinaemic demyelinating neuropathy - Růzicka, Evzen; Jech, Robert; Zárubová, Katerina; Roth, Jan; Urgosík, Dusan (Movement disorders, 2003)
We demonstrate the effect of deep brain stimulation of the ventral intermediate thalamic nucleus on intractable action tremor, in a 72-year-old man suffering from neuropathy associated with monoclonal gammopathy.
Keywords: Magnetic Resonance Imaging; Tremor; magnetická rezonanční tomografie; Humans; demyelinizační nemoci; mapování mozku; Paraproteinemias; Aged; senioři; lidé; Electromyography; Electric Stimulation Therapy; Brain Mapping; tremor; Male; Demyelinating Diseases; paraproteinemie; Midline Thalamic Nuclei; imunoglobulin M; mužské pohlaví; nuclei mediani thalami; elektromyografie; Immunoglobulin M; elektrostimulační terapie